Simultaneous saccharification and fermentation of corncobs with genetically modified Saccharomyces cerevisiae and characterization of their microstructure during hydrolysis. Issue 3 (8th April 2016) - Song, Hui-Ting; Liu, Shi-Hui; Gao, Yuan; Yang, Yi-Min; Xiao, Wen-Jing; Xia, Wu-Cheng; Liu, Zi-Lu; Li, Rong; Ma, Xiang-Dong; Jiang, Zheng-Bing
ABSTRACT: Cellulose is an abundant natural polysaccharide that is universally distributed. It can be extracted from corncobs, which are inexpensive, easily accessible, renewable, and environmentally friendly. A common strategy for effectively utilizing cellulose is efficient heterogeneous expression of cellulase genes in Saccharomyces cerevisiae . However, the improvement of cellulose utilization is a relevant issue. Based on our previous findings, we constructed an integrated secretion expression vector, pHBM368- pgk, containing a constitutive promoter sequence. Three genetically modified S. cerevisiae strains containing heterologous β-glucosidase, exoglucanase, and endoglucanase genes were constructed. The results of a 1-L bioreactor fermentation process revealed that the mixed recombinant S. cerevisiae could efficiently carry out simultaneous saccharification and fermentation (SSF) by using corncobs as the sole carbon source. The ethanol concentration reached 6.37 g/L after 96 hours of fermentation, which was about 3 times higher than that produced by genetically modified S. cerevisiae with the inducible promoter sequence. To investigate the microstructure characteristics of hydrolyzed corncobs during the fermentation process, corncob residues were detected by using a scanning electron microscope. This study provides a feasible method to improve the effect of SSF using corncobs as the sole carbon source.